Ciudad y deseo. Exclusión y diversidad: del barrio a la metrópolis - Pulgar P., Claudio (Revista INVI, 2016)
Felipe Corvalán, Diego Vallejos (Eds.) Ciudad y deseo. Exclusión y diversidad: del barrio a la metrópolis (2010)